2023
DOI: 10.3390/polym15112491
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Degradation of Silk Fibroin Hydrogels Exposed to Neuroinflammatory Environments

Abstract: Central nervous system (CNS) diseases represent an extreme burden with significant social and economic costs. A common link in most brain pathologies is the appearance of inflammatory components that can jeopardize the stability of the implanted biomaterials and the effectiveness of therapies. Different silk fibroin scaffolds have been used in applications related to CNS disorders. Although some studies have analyzed the degradability of silk fibroin in non-cerebral tissues (almost exclusively upon non-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…Previously, we have found a marked resistance of SF hydrogels to degradation in saline solutions. 10 Under these pseudophysiological conditions (PBS) and along 7 days of analysis, we found that the SF hydrogel weight, and the secondary structure (βsheet content) quantified by ATR-FTIR, remained constant, and both parameters were only impaired by enzymatic digestion (proteinase K). This result agrees with previous observations, where the deswelling ratio of SF hydrogels (inferred from the analysis of weight) in PBS was negligible, 38 suggesting that the mechanism driving the delivery of molecules from pure SF hydrogels in PBS is unlikely to be due to progressive matrix erosion or changes in secondary structure.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Previously, we have found a marked resistance of SF hydrogels to degradation in saline solutions. 10 Under these pseudophysiological conditions (PBS) and along 7 days of analysis, we found that the SF hydrogel weight, and the secondary structure (βsheet content) quantified by ATR-FTIR, remained constant, and both parameters were only impaired by enzymatic digestion (proteinase K). This result agrees with previous observations, where the deswelling ratio of SF hydrogels (inferred from the analysis of weight) in PBS was negligible, 38 suggesting that the mechanism driving the delivery of molecules from pure SF hydrogels in PBS is unlikely to be due to progressive matrix erosion or changes in secondary structure.…”
Section: Discussionmentioning
confidence: 75%
“…At a confluence of approximately 80%, BV2 cells were polarized toward a proinflammatory phenotype using Escherichia coli O111:B4 lipopolysaccharide (LPS, Sigma-Aldrich, L3024) at 100 ng/mL, following the procedure described by Yonesi and colleagues. 10 Cells were divided into different groups: −LPS −TGF-β-1, +LPS − TGF-β-1, +LPS + TGF-β-1 (recombinant TGF-β-1 was used at 10 ng/ mL), and +LPS + TGF-β-1 released from SF hydrogels at two concentrations (2 and 6%) with two different release time periods (0−1 and 3−7 d). The control media (−LPS − TGF-β-1, +LPS − TGF-β-1, and +LPS + TGF-β-1) were composed of DMEM supplemented with 2% FBS, 1% P/S, and 2 mM l-Gln.…”
Section: = • K Tmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the specific requirements vary based on the classification of the woundhealing product. A real case is represented by silk fibroin, a 100% biocompatible natural protein, totally free of any dangerous particle/molecule, with intrinsic antioxidant and reparative properties [146][147][148]. A clear candidate for natural polymer-based class I woundcare products.…”
Section: European Regulatory Issuesmentioning
confidence: 99%
“…However, the specific requirements vary based on the classification of the wound healing product. A real case is represented by silk fibroin, a 100% biocompatible natural protein, totally free of any dangerous particle/molecule, with intrinsic antioxidant and reparative properties [104] [105]. A clear candidate for natural polymer-based class I wound care products.…”
Section: European Regulatory Issuesmentioning
confidence: 99%